Nova Alta Paulista, 1930-2006: entre memórias e sonhos. Do desenvolvimento contido ao projeto político de desenvolvimento regional - Gil, Izabel Castanha [UNESP] (2007)
Development, despite the completion the term incites, occurs unequally in the midst of different areas and regions. According to the monopolistic logic that bases the social and economical process, society understakes the environment wich we are daily exposed to Nova Alta Paulista, located in the farwest of the state of São Paulo, was developed in the mid of the twentieth century, together with the urban industrialization on course in the metropolitan area in state control. External factors, such as the international conjuncture, besides the governmentþs move inspired by the national development trend, combined with internal factors, such as certain characteristics of the environment, local policies, and the predominance of a resistant conception to the consolidation of regional debates, contributed to a minor socioeconomical situation in the context of the state. Current affairs are leading us to important changes on environmental and territorial organization under the tendency to renewable sources of energy. Such fact demands reflection and study on its impact over development in the region. In this study, the objectives were to analyse how the socioeconomical development of Nova Alta Paulista took place to understand its current face; to examine the adjustment to the idea of a suppressed region to designate its socioeconomical and political cultural characteristics; to make use of a new approach that suprpasses the conception of territory, conceiving it as a social development which results from the conception of region to a territorial notion; to verify If the idea of regional development, named endogeneous development, will be able to territorialize, beginning with the socioeconomical actions under taken by local parties and segments in conflict with current hegemonical powers... (Complete abstract, click electronic address below)